Recent trends in botanical research - Gohil, R. N.; University of Kashmir. Department of Botany; All India Seminar on New Approaches to Plant Science Researches (1982 : Department of Botany, University of Kashmir) (Jodhpur : Scientific Publishers, 1985)
Papers presented at the All India Seminar on New Approaches to Plant Science Researches, organized by the Dept. of Botany, University of Kashmir, October 11-13, 1982.
Keywords: Botany -- Congresses; Botany -- Research -- India -- Congresses; Plant physiology -- Congresses; Plant cytogenetics -- Congresses; Plants -- Effect of radiation on -- Congresses; Plant ecology -- Congresses